2019
DOI: 10.1002/pro.3589
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome protection by ABC‐F proteins—Molecular mechanism and potential drug design

Abstract: Members of the ATP-binding cassette F (ABC-F) proteins confer resistance to several classes of clinically important antibiotics through ribosome protection. Recent structures of two ABC-F proteins, Pseudomonas aeruginosa MsrE and Bacillus subtilis VmlR bound to ribosome have shed light onto the ribosome protection mechanism whereby drug resistance is mediated by the antibiotic resistance domain (ARD) connecting the two ATP binding domains. ARD of the E site bound MsrE and VmlR extends toward the drug binding r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 45 publications
2
37
0
4
Order By: Relevance
“…The lin gene was detected in all the analyzed strains and encoded for a lincomycin resistance ABC-F type ribosomal protection protein, a member of the ATP-binding cassette F (ABC-F) proteins ( 38 ). We did not find descriptions of this mechanism in L. monocytogenes , but we did find the lin gene in almost all genomes of this species in NCBI Pathogen Detection Isolates Browser ( https://www.ncbi.nlm.nih.gov/pathogens/ ) suggesting that this mechanism could be involved in the natural resistance to lincomycin.…”
Section: Discussionmentioning
confidence: 99%
“…The lin gene was detected in all the analyzed strains and encoded for a lincomycin resistance ABC-F type ribosomal protection protein, a member of the ATP-binding cassette F (ABC-F) proteins ( 38 ). We did not find descriptions of this mechanism in L. monocytogenes , but we did find the lin gene in almost all genomes of this species in NCBI Pathogen Detection Isolates Browser ( https://www.ncbi.nlm.nih.gov/pathogens/ ) suggesting that this mechanism could be involved in the natural resistance to lincomycin.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, using large-scale sequencing of pooled genomic DNA of 262 strains, only two macrolide-related resistance genes, mphE and msrE , were identified in seven and four P. aeruginosa strains, respectively. This finding indicated that the known macrolide resistance genes are not prevalent in clinical P. aeruginosa isolates, although this was not the first time these two genes have been detected in P. aeruginosa ( Ding et al 2018 ; Ero et al 2019 ).…”
Section: Discussionmentioning
confidence: 87%
“…The mphE gene encodes a macrolide-2’-phospho-transferase, an intracellular enzyme with the ability to transfer the γ-phosphate of one nucleotide triphosphate to the 2’-OH group of macrolide compounds, thereby destroying the critical interaction between macrolides and A2058 ( Fyfe et al 2016 ). The msrE gene belongs to the ABC-F subfamily of ATP-binding cassette protein, which mediates a recently described new mechanism of resistance to macrolides ( Janvier et al 2017 ; Ero et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…One group of bacterial ABCFs, which are termed antibiotic resistance (ARE) ABCFs (Dorrian & Kerr, 2009), confer resistance to antibiotics that bind to the 50S subunit of the bacterial ribosome (Ero et al , 2019; Ousalem et al ., 2019; Sharkey & O’Neill, 2018; Wilson et al ., 2020). Characterized ARE ABCFs are found predominantly in Gram-positive bacteria, including human and animal pathogens, typically have a restricted host specificity, and can be further divided into eight subfamilies (Allignet et al , 1992; Murina et al ., 2019; Wilson et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%